The Dialectic Of Oral Narrative As A Leading Source In The Codification And Justification Of Historical Events - Sabah Abid, Tahar Ibrir, Messaoud Himed (Journal of Informatics Education and Research, 2025)
Objectives: This research paper investigates the dialectical relationship between oral narration and oral history as foundational sources of historical and legal knowledge. It seeks to elucidate how oral narratives frequently marginalized within traditional historiography can play a pivotal role in the codification, interpretation, and legitimation of historical events. Methods: The study adopts a historical–legal methodology grounded in qualitative analysis. It combines a critical review of prior scholarship with the systematic collection of oral testimonies through semi-structured interviews. These testimonies are then evaluated against authenticated archival materials to assess their evidentiary reliability and historical–juridical relevance. Results: Findings indicate that oral narration, when subjected to rigorous methodological scrutiny, can constitute a credible and complementary evidentiary corpus within historical research. The analysis demonstrates that well-documented oral testimonies provide interpretive depth, particularly in reconstructing events where official records have been lost, censored, or selectively preserved.. Conclusions: The study concludes that integrating oral narration within the broader framework of historical inquiry not only enriches the epistemological foundations of history but also reinforces the principles of historical justice by amplifying marginalized voices and legitimizing suppressed experiences. Such integration ensures that historical reconstruction adheres both to documentary authenticity and to ethical responsibility in preserving collective memory.